Music and students' conceptions of the social role attributed to women (Research, Society and Development, 2020)
Understanding the importance of music as a form of expression present in society since the oldest civilizations, this article aims to reflect on the power relations present in society, which generally place women in a hierarchical position inferior to men, characterized by submission. For this purpose, it is a qualitative research, using the interactive technique of participant observation as a data collection instrument, as well as making use of image and sound resources for its respective registration. The approach is also done through bibliographic research, based on the concept of gender for the purpose of understanding the social role attributed to women throughout human history. For this, we will use an experience report held at a school in the Baixada Fluminense, whose music analysis has contributed to awakening the students' criticality. Through the studies carried out and the lived experience it is possible to understand that even in view of the various achievements obtained by women over the years, the role assigned to them in contemporary times is still associated by many individuals with marriage and motherhood. Thus, it is extremely important to debate these issues in the school space, so that we can contribute to the deconstruction of concepts associated with gender, which have been causing an increase in violence aimed at those who do not obey the standards determined by society.